Assessment on the population and health professionals’ knowledge on the cornea donation process - Krieger, Michele Aparecida Lonardoni; Novellino, Andrea Mora De Marco; Mariushi, Ana Cláudia Munemori; Moreira, Hamilton (Brazilian Journal of Transplantation, 2009)
The corneal transplant is now the most common type of tissue transplant, and it has been growing each year in Brazil. However, there is a lack of knowledgeable donors, resulting from misinformation on part of the professionals in the health field. Purpose: To assess the knowledge the laity, health professionals and medical doctors on the cornea donation process; they were argued aiming to identify possible flaws in the reception process. Methods: Along a Cornea Donation Campaign developed in Curitiba-PR, medical doctors, health professionals and laity people were asked to answer a survey with subjective knowledge on the cornea donation. Results: An amount of 588 people responded to the questionnaire, being 313 laymen, 157 health professionals, and 118 physicians. From that total, 94.4% support the cornea donation, being 91.3% of the laity, 96.1% of the health professionals, and 100% of the medical doctors. Among the laity, 83% would donate their corneas compared to 83.4% of health professionals and 97.4% of medical doctors. When subjective questions were replaced by knowledge questions, there was a high rate of in doubt respondents. Questions such as "age limit for donation," "understanding the function of the eye bank" and "amount of people waiting for a transplant" had indeterminate rates of 95.8%, 28.1% and 64.8%, respectively. Conclusion: It was observed that there is a deficiency of information on the cornea transplantation, even among medical doctors and health professionals. It is suggested to focus on instructing the professional approach team in order to increase both the cornea uptake and the amount of corneal transplants, as well as to stimulate informative campaigns for the population.